2019
DOI: 10.2147/tcrm.s218934
|View full text |Cite
|
Sign up to set email alerts
|

<p>Influence Of Uncertainty, Depression, And Social Support On Self-Care Compliance In Hemodialysis Patients</p>

Abstract: PurposeThis study was conducted to examine the associations among uncertainty, depression, social support, and self-care compliance in patients undergoing hemodialysis, and to identify the factors influencing self-care compliance.MethodsA convenience sample of 152 patients receiving hemodialysis was selected. Data were analyzed using descriptive statistics, independent t-test, ANOVA, Pearson correlations, and hierarchical regression analysis with the SPSS 23.0 program.ResultsParticipants performed a moderate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 35 publications
7
24
3
6
Order By: Relevance
“…According to the findings, treatment adherence behaviors are associated with the education level. Recently, similar to our results, Kim has reported that with increasing the education level, treatment adherence behaviors are improved [ 31 ]. We can mention that patient noncompliance is attributed to personal qualities of patients, such as forgetfulness, lack of willpower or discipline, or low level of education [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to the findings, treatment adherence behaviors are associated with the education level. Recently, similar to our results, Kim has reported that with increasing the education level, treatment adherence behaviors are improved [ 31 ]. We can mention that patient noncompliance is attributed to personal qualities of patients, such as forgetfulness, lack of willpower or discipline, or low level of education [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Priyanti (2015) also showed that 51.3% of patients receive less support. Furthermore, according to Kim and Kim (2019), the mean value of social support for hemodialysis patients was 44.9 in the range of 12-60.…”
Section: Discussionmentioning
confidence: 99%
“…Further complications of fatigue in patients on hemodialysis have been associated with poor quality of life and lower survival rates due to decreased physical and psychological activity (12,13). Research by Abd El-Nasser Ali (14) and Vasilopoulou et al (15) found that hemodialysis patients who have significant problems with fatigue and depression can also affect the poor quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Abd El-Nasser Ali (14) and Vasilopoulou et al (15) found that hemodialysis patients who have significant problems with fatigue and depression can also affect the poor quality of life. Poor quality of life in hemodialysis patients can increase cardiovascular and suicide risks, therefore this will become a big problem if not given proper management (13,16,17).…”
Section: Introductionmentioning
confidence: 99%